It's the end of the competition: when social comparison is not always motivating for goal achievement - Chan, Elaine (2022)
Nowadays consumers can easily connect with others who are pursuing similar goals via smart devices and mobile apps. This technology also enables them to compare how well they are doing relative to others in a variety of contexts, ranging from online gaming to losing weight to loyalty programs. This research investigates consumers' motivation to achieve a goal when they compare themselves with a superior other who has already attained the goal. Building on the literature on social comparison, and on competition in particular, we find that consumers are less motivated when the superior other has attained the goal compared to when the superior other is just ahead, keeping the relative distance equal. This negative effect on motivation is evident even in situations in which consumers can still attain the same goal as the superior other. We argue and demonstrate that this effect occurs because the other's goal attainment limits consumers' prospect to compete and overtake the superior other. Six experimental studies show evidence for this effect in hypothetical loyalty programs and behavioral task completion. These findings provide a deeper understanding of the motivational effect of social comparison, which have implications for marketing managers and public policy makers.